Employee Engagement in Swedish Public Sector Organizations: The Impact of Organizational and Social Factors on Employee Net Promoter Scores - Löfstrand, Pär; Wall, Erika; Selander, John; Nordenmark, Mikael; Vinberg, Stig (Scandinavian Journal of Public Administration, 2025)
Many public organizations are striving to develop sustainable workplaces with a focus on employee engagement. Different models are used in different countries and contexts to measure employee engagement. In Swedish public sector workplaces, a model consisting of three components is used: motivation, leadership and strategic management. There is a need to enhance understanding of the model and its relation to employee advocacy. This study aims to provide greater understanding of employee engagement dynamics in the public sector, including team climate and work-life balance components, and how this relates to aspects of employee advocacy. Statistical analyses of key components were carried out using survey results from 6 020 employees and managers in municipal workplaces. The findings highlight significant relations between the components investigated and the employee-advocacy-related measurement employee Net Promotor Score. Based on OLS regressions, motivation emerged as the most influential component, followed by leadership. It was possible to classify the participants into three categories: Promoters, Passives and Detractors. The promoters exhibited higher scores on all components, and managers had higher scores on several components compared to employees. The results confirm that it is important to use a multi-dimensional approach when studying employee engagement in public sector workplaces.